Analysis of surface tension driven flow and solidification behavior in laser linear welding of stainless steel. (March 2020) - Li, Zhiyong; Yu, Gang; He, Xiuli; Li, Shaoxia; Tian, Chongxin; Dong, Binxin
Highlights: Qualitative study of the mechanism of surface tension driven flow. Analysis of driving forces and driving mechanism. Quantitative investigation of surface tension and surface shear stress distribution. 3D distribution of solidification parameters. Semi-qualitatively prediction of solidified microstructure. Abstract: A transient three-dimensional thermal-fluid-metallurgy model was proposed to study the surface tension driven flow and welding metallurgical behavior during laser linear welding of 304 stainless steel. Numerical simulation and experimental method were both used to investigate the thermal behavior, surface tension driven flow, driving mechanism and solidification characteristics. The temperature related driving force was qualitatively analyzed, and surface tension and surface shear stress were quantitatively studied. Numerical method and dimensional analysis were also carried out to understand the importance of different driving forces, respectively. The metallurgical model was sequentially coupled to the thermal-fluid model to calculate four solidification parameters. Temperature gradient was observed to be much larger at the front of the melt pool due to the effect of thermal conductivity, and decreased from center to the periphery. Both the surface tension and surface tension driven flow were found smaller in the central area. The maximum shear stress may reach 2500 N/m 2 and pushed an intense outward convection. The solidification parameters were used to predict the solidified morphology, and the prediction was well validated by experimental results. The obtained basic conclusions in this work demonstrated that this study of thermal-fluid-metallurgical behavior could provide an improved understanding of the surface tension driven flow and solidification behavior inside the melt pool of welding and additive manufacturing process.